2019
DOI: 10.3389/fmicb.2019.01334
|View full text |Cite
|
Sign up to set email alerts
|

A Genomotaxonomy View of the Bradyrhizobium Genus

Abstract: Whole genome analysis of the Bradyrhizobium genus using average nucleotide identity (ANI) and phylogenomics showed the genus to be essentially monophyletic with seven robust groups within this taxon that includes nitrogen-fixing nodule forming bacteria as well as free living strains. Despite the wide genetic diversity of these bacteria no indication was found to suggest that the Bradyrhizobium genus have to split in different taxa. Bradyrhizobia have larger genomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 95 publications
4
74
0
Order By: Relevance
“…2 and Fig. S6) as Bradyrhizobium spp., which is consistent with the results of previous studies on peanut rhizobia isolated from China and Argentina [3,29,31]. The identification of most of the isolates into genospecies corresponding to B. liaoningense, B. arachidis, B. guangdongense and B. yuanmingense demonstrated that these species are common peanut rhizobia in China and in other countries [3,6,14,23,28,29,38,42].…”
Section: Unique Community Structure Of Peanut Rhizobia In the Samplinsupporting
confidence: 91%
See 2 more Smart Citations
“…2 and Fig. S6) as Bradyrhizobium spp., which is consistent with the results of previous studies on peanut rhizobia isolated from China and Argentina [3,29,31]. The identification of most of the isolates into genospecies corresponding to B. liaoningense, B. arachidis, B. guangdongense and B. yuanmingense demonstrated that these species are common peanut rhizobia in China and in other countries [3,6,14,23,28,29,38,42].…”
Section: Unique Community Structure Of Peanut Rhizobia In the Samplinsupporting
confidence: 91%
“…I identified in the present study were newly recorded as peanut rhizobia and their biogeographic distribution was first reported here. These results demonstrated that (1) the main peanut rhizobia are restricted to the Bradyrhizobium species, which belong to the B. japonicum supergroup or superclade, which was classified recently [1,31]; (2) the peanut nodulating bradyrhizobia have been diversifying in different regions under the selection of soil conditions; and (3) the community structure of peanut bradyrhizobia is also shaped by the monoculture history, competitive ability, and soil properties.…”
Section: Unique Community Structure Of Peanut Rhizobia In the Samplinmentioning
confidence: 92%
See 1 more Smart Citation
“…), and L. uliginosus have been shown to be nodulated by closely related bradyrhizobia that are in the same cross-inoculation group [9,16,17]. The genus Bradyrhizobium comprises highly diversified bacteria, with 39 described species thus far [18][19][20], including some photosynthetic strains [21][22][23]. The 16S rRNA gene is very conserved within this genus and, like the symbiotic genes, has been shown to be laterally transmitted [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Bradyrhizobium communities are also abundant in many soils where legumes are absent, often acting as endophytes of different plants (Vanlnsberghe et al 2015). The studies have revealed that the genus Bradyrhizobium is separated into seven lineages, including symbiotic as well non-symbiotic bacteria (Avontuur et al 2019;Ormeño-Orrillo and Martínez-Romero 2019). A large number of species in Bradyrhizobium has been recognized, however the list of species in this genus will probably be still growing due to the rapid development of molecular tools and the huge diversity of this genus (Stępkowski et al 2018;de Lajudie et al 2019).…”
Section: Introductionmentioning
confidence: 99%